Risk Factors of Carpal Tunnel Syndrome for Male Patient Undergoing Carpal Tunnel Release - Lee, Jun-Ku; Lee, Soo-Hyun; Kim, Banghyun; Jung, Kyunghun; Park, Inkeun; Han, Soo-Hong (Handchirurgie · Mikrochirurgie · Plastische Chirurgie, 2018)
Introduction Although the major cause of carpal tunnel syndrome (CTS) remains idiopathic, many male CTS patients are clinically different from female patients and often have specific risk factors associated with their conditions. An accurate analysis of such propensity has yet to be established. The purpose of this study is to compare male and female patients by analyzing the risk factors associated with CTS patients who underwent surgical treatment, with focus on their occupation.Patients/Material and Methods retrospective chart review of 818 patients with CTS was performed to identify the associated risk factors. Patients were stratified by gender: female (n = 707, 86.4 %) and male (n = 111, 13.6 %). The mean patient age was 54.5 (range: 16–85 yr.) for all groups. The medical history and risk factors of each patient was thoroughly reviewed by medical charts and telephone survey. We categorized the risk factors of CTS into 7 categories: anatomic, neuropathic, inflammatory, alteration of fluid balance, distal radius fracture associated, occupational risk factor related, and idiopathic. Occupations of CTS patients were divided into high risk occupations (vibratory tools, assembly jobs, and food processing and packaging jobs, and other occupations of repetitive wrist motion and forceful gripping) and nonrisk occupations. All variables were analyzed with chi-square or Fisher’s exact test for differences between men and women.Results The number of individuals with known risk factors of CTS was greater in male, compared to that of female patients; 97 (87.4 %) male patients had the risk factors of CTS, while 361 (51.1 %) female patients (p < 0.001) did. In subgroup analysis of risk factors, male patients had frequent risk factors in neuropathic, inflammatory, and alteration of fluid balance (p < 0.001). Occupational risk was strongly associated with male gender (p < 0.001).Conclusion Male CTS patients who underwent surgery are more likely to have a reason and have many occupational risk factors than women.
Keywords: carpal tunnel syndrome; risk factors; male patients; carpal tunnel release